Romans introduction, Authorized Version, Revised version with notes, index and map - Garvie, Alfred E. 1861-1945 (Edinburgh, Scotland T.C. and E.C. Jack)
Includes index.
Original owner has pasted photo and possibly newspaper obit into front cover (A.C.W. 18/5/1945).
Keywords: Bible. N.T. Romans -- commentaries